Implementation of the Village Sustainable Development Goals Policy (Study in Sri Mulya Village, Sinar Peninjauan District, Oku Regency, South Sumatra Province - Diah Ayu Permatasari; Muhammad Shobaruddin; Tjahjanulin Domai (Faculty of Law, Universitas Pekalongan, 2023)
The aim of this village sustainable development research is to describe the implementation of village sustainable development goals in Sri Mulya Village, Sinar Peninjauan District, OKU Regency, South Sumatra Province. Apart from that, this research also aims to identify factors that can support or hinder the implementation of village sustainable development goals in Sri Mulya Village, Sinar Peninjauan District, OKU Regency, South Sumatra Province. The theory in this research uses the theory put forward by Soren C. Winter (2006). According to Winter, the success of implementing a policy can be seen based on 3 variables, namely the behavior of inter-organizational relations with the dimensions of organizational commitment and inter-organizational coordination, the behavior of implementers (lower level bureaucracy) with the discretionary dimensions and the behavior of the target group with the dimensions of positive and negative responses. The type of research used is qualitative descriptive research. The research results show that the implementation of village sustainable development goals in Sri Mulya Village as seen from the 3 variables of Soren C. Winter (2006) has not been implemented optimally with problems including: Commitment is only verbal because there is no concrete action which causes there is no sense of awareness to be involved, Coordination between organizations is limited to reporting without any feedback as an effort to provide guidance on the implementation of village sustainable development goals in Sri Mulya Village. The village government takes the decision as a form of discretion. The decision taken was to continue updating the data with existing human resources, because there were elements implementing data updates who should have been involved but did not help. The community gave a positive response in the form of cooperation during village data collection. The negative response is that there are still doubts from the community about the Village Sustainable Development Goals programKeywords:Village Sustainable Development Goals, Implementation, Community Welfare